Evaluation of Dynamic Voltage and Frequency Scaling on Digital Pre-distortion - Chen,Wenyue (2025)
Power amplifiers play a crucial role in wireless communication systems. However, they can achieve high efficiency only when operating in the nonlinear region. To maintain linear output while operating in this region, several techniques have been developed, among which digital pre-distortion (DPD) is one of the most widely used. In this thesis, we designed and analyzed a digital predistortion (DPD) system consisting of eight lookup-table (LUT)-based modules. This work began with the development of a DPD architecture to ensure the system effectively compensates for nonlinearities. Based on this design, we evaluated its power consumption at various operating frequencies and supply voltages, gaining insight into its performance and efficiency. This work evaluates the impact of dynamic voltage and frequency scaling (DVFS) on the DPD. With the increasing demand for high energy efficiency and wide bandwidth in wireless systems, DVFS has become an essential technique to balance power consumption and signal quality. However, dynamic operating conditions introduce time-varying nonlinear behaviors that challenge the adaptability of traditional DPD algorithms. This thesis analyzes the sensitivity of DPD models under varying voltage and frequency conditions and check if power consumption by DPD algorithm can be reduced by employing DVFS.
Keywords: digital pre-distortion (DPD); dynamic voltage and frequency scaling (DVFS); power amplifier (PA); nonlinear distortion; adaptive linearization; dynamic power